The Optimum Sulfur Recovery Process From North Gas Company Sour Acid Gas: A Case Study and Simulation - Abdulrahman, Ribwar K.; Zangana, Mohammed H.; Srivastava, Ganank (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
The North Gas Company in Kirkuk, Iraq produces a sour gas stream that is loaded with considerable amounts of H2S and CO2, at concentrations of 2.95% and 2.54%, respectively. A previous study successfully treated this sour gas stream and produced a sweet gas stream by adopting a natural gas sweetening process using ProMax process simulation software. However, this process also produced an acid gas stream that was loaded with a considerable amount of H2S. The acid gas stream is processed in a sulfur recovery unit to protect the environment. The Claus process is the major technology used to produce elemental sulfur from H2S and SO2 gases. This study examines this process to treat the acid gas stream and recover the elemental sulfur, using ProMax simulation software developed by Bryan Research and Engineering, LLC. Moreover, the simulation model was successful in reducing the amount of H2S from 872.5 kg/h to 60.5 kg/h by adopting two Claus bed reactors to increase the process efficiency. Furthermore, process optimization was also adopted to find out the optimum Claus reactor bed operating temperature at 215°C.